2002
DOI: 10.1016/s0022-5347(05)64836-7
|View full text |Cite
|
Sign up to set email alerts
|

p53 as a New Prognostic Factor for Lymph Node Metastasis in Penile Carcinoma: Analysis of 82 Patients Treated with Amputation and Bilateral Lymphadenectomy

Abstract: Immunoreactivity of p53 is an independent factor for lymph node metastasis. The association of positive p53 with positive HPV DNA was related to a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(36 citation statements)
references
References 22 publications
0
33
1
Order By: Relevance
“…The mutant protein accumulates in the nucleus of tumor cells and is identified by immunohistochemical reaction. The frequency of the overexpression of the p53 protein product was reported to be 41-89% in penile squamous cell carcinomas (8,26,27). Our data showed that overexpression of the p53 protein product was detected in 37 (72.5%) of 51 penile cancer cases with and without HPV infection.…”
Section: Discussionmentioning
confidence: 48%
“…The mutant protein accumulates in the nucleus of tumor cells and is identified by immunohistochemical reaction. The frequency of the overexpression of the p53 protein product was reported to be 41-89% in penile squamous cell carcinomas (8,26,27). Our data showed that overexpression of the p53 protein product was detected in 37 (72.5%) of 51 penile cancer cases with and without HPV infection.…”
Section: Discussionmentioning
confidence: 48%
“…The overall percentage of p53 positive carcinomas is remarkably high (91%) compared to reported values ranging from about 25% to 65% (26)(27)(28)(29)(30). In HPV positive tumours, p53 was detected in 100% of samples, 50% of them having a very strong (group II) estimated intensity.…”
Section: Discussionmentioning
confidence: 66%
“…This method has been used before for detection of mutated p53 in genital and bladder cancer (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reliable staging information can only be acquired through surgical procedures with subsequent histologic examination of the inguinal lymph nodes. The pathologic factors with known prognostic value, other than the presence of lymph node metastasis, include tumor thickness, grade, histologic type, lymphovascular embolization, presence of koilocytosis and stage (4)(5)(6). On the clinical nodal status there is a dilemma: a significant number of patients with palpable lymph nodes do not have metastasis, in the other hand, 20% of patients with clinically non-suspicious nodes present micrometastasis at pathological examination.…”
Section: Introductionmentioning
confidence: 99%